Role of PGC-1α mediated synaptic plasticity, mitochondrial function, and neuroinflammation in the antidepressant effect of Zi-Shui-Qing-Gan-Yin - Zhu, Wen; Zhang, Wen; Yang, Feng; Cai, Min; Li, Xiangting; Xiang, Yijin; Xiang, Jun; Yang, Yunke; Cai, Dingfang (Frontiers in Neurology, 2023)
Depression is the most prevalent psychiatric disorder, which needs deeper mechanism researches and effective therapy. Zi-Shui-Qing-Gan-Yin (ZSQGY) is a traditional Chinese medicine decoction which has been widely used in China in the treatment of depressive symptoms. The aim of the study was to examine the anti-depressive effects of ZSQGY and the possible mechanism of action in monosodium glutamate (MSG) induced depressive model and corticosterone (CORT)-induced PC12 cell model. Liquid chromatography-mass spectrometry (LC-MS) was performed to determine the major compounds in water extract of ZSQGY. The depressive behaviors were evaluated by field swimming test (FST), sucrose preference test (SPT) and open field test (OFT). The Golgi staining and the transmission electron microscopy (TEM) were performed to display the alterations of synaptic ultrastructure. The mitochondrion function and inflammatory factors were also quantified. The changes of peroxisome proliferator-activated receptor-γ co-activator 1α (PGC-1α) expression were evaluated. The results in this study demonstrated that ZSQGY significantly improved the depressive behaviors. ZSQGY also reversed the changes of synaptic plasticity, improved mitochondrion function and reduced the levels of inflammatory factors. The neuroprotective effects were accompanied with the increased expression of PGC-1α. However, the beneficial changes were reversed after the inhibition of PGC-1α. These results indicated that ZSQGY effectively could improve depressive behaviors via the mechanisms that regulating synaptic structural plasticity, improving mitochondrion function and alleviating neuroinflammation, which could, or partly attribute to the regulation on PGC-1α.